2014 IEEE International Reliability Physics Symposium 2014
DOI: 10.1109/irps.2014.6860630
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cu TSVs on BEOL metal and dielectric reliability

Abstract: Cu pumping of through silicon vias (TSV) may result in deformations of the Cu/low-k interconnect wiring above the TSVs and affect the back-end-of-line (BEOL) metal and dielectric reliability. We investigate the impact of Cu TSVs on the BEOL reliability, including stress induced voiding (SIV) of Cu vias on top of the TSV and the dielectric reliability of both interand intralevel low-k materials in Cu damascene interconnects.Possible solutions to mitigate the reliability risks are also discussed. Keywords-BEOL r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The TSV liner is a 200nm thick O3 TEOS dielectric. Stress-induced-voiding failure rates under vias placed at different locations above a TSV for the case where the TSV is integrated before the BEOL and thus appears directly below the first metal layer (M1) [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TSV liner is a 200nm thick O3 TEOS dielectric. Stress-induced-voiding failure rates under vias placed at different locations above a TSV for the case where the TSV is integrated before the BEOL and thus appears directly below the first metal layer (M1) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the use of more vias connected in parallel is recommended as an effective mitigation strategy against SIV. In general, the impact of the TSV presence on BEOL TDDB is low, as shown in [22] at least for BEOL layers processed in the 65nm technology node. As for FEOL, it can be concluded that BEOL reliability is not impacted by the TSV presence if the TSV integration processes and the interconnect layout are optimized.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The literatures investigated the effects of annealing temperature, Cu electroplating parameter, and other factors on pop‐out phenomenon of TSV‐Cu. Moreover, the effects of Cu pop‐out on the dielectric layers directly above the TSV structure and the effects of TSV proximity on devices have been investigated. However, no literature was found to study the impact of TSV structure on BEOL layers around the TSV during the annealing process according to the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%